Budd-Chiari syndrome in a young patient with celiac sprue: A case report - Ahmet DANALIOĞLU; Şule POTUROĞLU; Mine GÜLLÜOĞLU; Kadir DEMİR and Fatih BEŞIŞIK and Yılmaz ÇAKALOĞLU and Uğur ÇEVİKBAŞ and Atilla ÖKTEN (Turkish Journal of Gastroenterology, 2019)
-